Do financial conglomerates create or destroy economic value? - Schmid, Markus M.; Walter, Ingo (Journal of Financial Intermediation, 2009)
This paper investigates whether functional diversification is value-enhancing or value-destroying in the financial services sector, broadly defined. Based on a U.S. dataset comprising approximately 4060 observations covering the period 1985–2004, we report a substantial and persistent conglomerate discount among financial intermediaries. Our results suggest that it is diversification that causes the discount, and not that troubled firms diversify into other more promising areas. In addition, the discount applies to all financial services activity-areas with the exception of investment banking and is stable over different combinations of financial activity-areas with the exception of commercial banking units combined with insurance companies and/or investment banking activities.